DentistsÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ Preferences of Anterior Tooth ProportionÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬ÂA Web-based Study - David R. Burns, DMD,1 Peter C. Moon, PhD,2 Neal P. Webster, DDS,3 (Blackwell Synergy, 2000)
This study evaluated the retention of prefabricated parallel-sided dowels luted with resin cement in extracted teeth that were obturated with gutta percha using a eugenol sealer or a calcium hydroxide sealer.